HUBUNGAN KETERLIBATAN ORANG TUA DALAM BELAJAR DENGAN PRESTASI AKADEMIK SISWA SEKOLAH DASAR NEGERI 07 PAGI KELURAHAN TEGAL ALUR JAKARTA BARAT - Eka Yosi Azizah; Dameria Br Saragih; Ns. Ernawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Parental involvement is one of the factors that plays an important role in improving the academic achievement of elementary school students. This involvement includes assisting children with learning, providing motivation, supervising learning activities, providing learning facilities, and maintaining communication with the school. This study employed a descriptive quantitative design with a cross-sectional approach. The study involved 125 respondents selected using the total sampling technique. Data on parental involvement were collected using a questionnaire, while data on academic achievement were obtained from students' report card documentation. Data were analyzed using the Spearman Rank correlation test with a significance level of α = 0.05. The results showed that most parents had a high level of involvement (67 respondents; 53.6%), and the majority of students had good academic achievement (71 respondents; 56.8%). The Spearman Rank test revealed a significant relationship between parental involvement in learning and students' academic achievement (r = 0.714; p < 0.001), indicating a strong positive correlation. These findings suggest that the higher the level of parental involvement in children's learning process, the better their academic achievement. In conclusion, parental involvement has a significant relationship with the academic achievement of elementary school students.